Dépossessions : le rôle de la chorégraphie dans A Dance of the Forests et The Bacchae of Euripides de Wole Soyinka - Kerry-Jane Wallart (Sillages Critiques)
This paper scrutinizes the part played by dancing in two plays by Soyinka where such an artistic practice is rather foregrounded. I shall attempt to understand how theatre might be reinforced by dancing, an immediate, a corporeal art, the intrusion of a dramaturgy that is freed from the text. I wish to show that it provides for a minimization of the necessity to make sense and allows the spectator to access the symbolical realm as understood by Baudrillard. A performance of possession may thus be staged which paradoxically corresponds to an absence both of interpretation and of any possible intention. The dispossession which is entailed by a sequence of dancing allows me to redefine the place as an absence thereof, and mimesis as pure opsis.